Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Antibacterial & antiplasmid activities of Helicteres isora L. - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Dhakephalkar, Prashant K.; Rojatkar, Supada; Shitole, Mahadeo G. (Indian Journal of Medical Research, 2010)
Background & objectives: The multiple drug resistance (MDR) is a serious health problem and major challenge to the global drug discovery programmes. Most of the genetic determinants that confer resistance to antibiotics are located on R-plasmids in bacteria. The present investigation was undertaken to investigate the ability of organic extract of the fruits of Helicteres isora to cure R-plasmids from certain clinical isolates. Methods: Active fractions demonstrating antibacterial and antiplasmid activities were isolated from the acetone extracts of shade dried fruits of H. isora by bioassay guided fractionation. Minimal inhibitory concentration (MIC) of antibiotics and organic extracts was determined by agar dilution method. Plasmid curing activity of organic fractions was determined by evaluating the ability of bacterial colonies (pre treated with organic fraction for 18 h) to grow in the presence of antibiotics. The physical loss of plasmid DNA in the cured derivatives was further confirmed by agarose gel electrophoresis. Results: The active fraction did not inhibit the growth of either the clinical isolates or the strains harbouring reference plasmids even at a concentration of 400 mu g/ml. However, the same fraction could cure plasmids from Enterococcus faecalis, Escherichia coli, Bacillus cereus and E. coli (RP4) at curing efficiencies of 14, 26, 22 and 2 per cent respectively. The active fraction mediated plasmid curing resulted in the subsequent loss of antibiotic resistance encoded in the plasmids as revealed by antibiotic resistance profile of cured strains. The physical loss of plasmid was also confirmed by agarose gel electrophoresis. Interpretation & conclusions: The active fraction of acetone extract of H. isora fruits cured R-plasmids from Gram-positive and Gram-negative clinical isolates as well as reference strains. Such plasmid loss reversed the multiple antibiotic resistance in cured derivatives making them sensitive to low concentrations of antibiotics. Acetone fractions of H. isora may be a source to develop antiplasmid agents of natural origin to contain the development and spread of plasmid borne multiple antibiotic resistance.
Keywords: antibacterial activity; Antibiotic resistance; antiplasmid activity; Helicteres isora; multiple drug resistance; plasmid-curing

Cytotoxic activity of 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda against human cancer cells - Shriram, Varsha; Kumar, Vinay; Kishor, P. B. Kavi; Suryawanshi, Sharad B.; Upadhyay, Ankur K.; Bhat, Manoj K. (Journal of Ethnopharmacology, 2010)
Ethnopharmacological relevance: Eulophia nuda L. (Orchidaceae) is a medicinally important terrestrial orchid used for the treatment of tumours and various health problems by the local healers throughout the Western Ghats region in Maharashtra (India). Aim of the study: To isolate the active molecule from Eulophia nuda and to study its cytotoxic potential against human cancer cells. Materials and methods: The crude methanolic extract of Eulophia nuda tubers was fractionated by stepwise gradient of the solvents chloroform-methanol to isolate the pure compound. Isolated pure compound was assessed for its cytotoxic potential against human breast cancer cell lines, MCF-7 and MDA-MB-231 using MTT assay. Structure elucidation of the isolated active compound was carried out by extensive spectroscopic analysis including (1)H NMR, (13)C NMR, NOESY, COSY, LC-MS and IR. Results: The isolated active molecule was identified as phenanthrene derivative 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol. This compound showed good antiproliferative activity against human breast cancer cell lines MCF-7 (91%) and MDA-MB-231 (85%) at 1000 mu g/ml concentration. Conclusion: 9,10-Dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda tubers showed good growth suppressive effect against human cancer cell lines MCF-7 and MDA-MB-231 making it a potential biomolecule against human cancer. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cytotoxic activity; Eulophia nuda; Phenanthrene derivatives

Phytochemical profile, anti-oxidant, anti-inflammatory, and anti-proliferative activities of Pogostemon deccanensis essential oils - Kumar, Vinay; Shriram, Varsha; Bhagat, Rani; Khare, Tushar; Kapse, Shivanjali; Kadoo, Narendra (3 Biotech, 2019)
Essential oils (EOs) obtained from aerial parts of Pogostemon deccanensis were analyzed for GC-MS profiling, and evaluated for antioxidant, anti-inflammatory, and anti-proliferative activities. GC-MS analysis revealed a total of 47 constituents, establishing the EOs rich in sesquiterpene with >20 sesquiterpenes constituting around 77% of the total EO yield. Major constituents included Curzerene (Benzofuran, 6-ethenyl-4,5,6,7-tetrahydro-3,6-dimethyl-5-isopropenyl-, trans-) (26.39%) and epi-Cadinol (22.68%), Ethanone, 1-(2,4,6-trihydroxyphenyl) (6.83%, Acetophenones), and Boldenone (3.47%, anabolic steroid). EOs found to be rich in phytochemicals attributed for antioxidant potentials of aromatic/medicinal plants, viz., flavonoids (2.71 mu g quercetin equivalents g(-1) EO), total phenols (3.94 mu g gallic acid equivalents (GAE) g(-1) EO), carotenoids (14.3 mu g -carotene equivalents g(-1) EO), and ascorbic acid (2.21 mu g ascorbic acid equivalents g(-1) EO). P. deccanensis EOs exhibited striking antioxidant activities assessed by wide range of assays including ferric reducing antioxidant potential (FRAP, 255.3 GAE at 2 mu g mL(-1) EO), total antioxidant activity (TAA, 264.3 GAE at 2 mu g ml(-1)) of EO, DPPH (65% inhibition at 2 mu g mL(-1)), and OH (58% inhibition at 2 mu g mL(-1)) scavenging. Interestingly, EOs showed considerably higher anti-lipid peroxidation activity than the standard antioxidant molecule ascorbic acid, with 50% protection by 1.29 mu g mL(-1) EO against 20.0 mu g mL(-1) standard. EOs showed strong anti-inflammatory activity with 50% inhibition at 1.95 mu g mL(-1) EO. The anti-proliferative activity of EOs was tested against mouse cancer cell line and the EOs proved a potent anti-proliferative agent with only 2.1% cell survival at 2 mu g mL(-1) EO, whereas the EOs were largely non-toxic-to-normal (non-cancerous) cells with approximately 80% cell survival at the 2 mu g mL(-1) EOs. This being the first attempt of phytochemical profiling and wide array of biological activities of P. deccanensis EOs holds significance as the striking activities were observed at very low concentrations, in some cases at lower than the commercial standards, and has, therefore, great potential for pharmaceutical or commercial exploration.
Keywords: Anti-inflammatory activity; Anti-proliferative activity; Antioxidants; Cytotoxicity; Essential oils